Antibacterial and cytotoxic effect of a novel biological Nano-silver fluoride synthesized from moringa oleifera leaf extract - Kadhem, Duaa J; Al Haidar, Aseel Haidar M.J. (Journal of Baghdad College of Dentistry, 2023)
Background: A great dental and biomedical interest had been paid to silver nanoparticles because of their antimicrobial activity. Objective: To evaluate the antimicrobial and cytotoxic activity of a newly developed Nano-silver fluoride that was synthesized from moringa oleifera leaf extract against S. mutants. Material and method: The green synthesis method was used to prepare Nano-silver fluoride from moringa oleifera leaf extract. The minimum inhibitory concentration and the minimum bactericidal concentration were evaluated using brain heart infusion plates, while the cytotoxicity was evaluated by the hemolytic activity. Results: Nano-silver fluoride had a bactericidal and bacteriostatic effect (MIC was 60 ppm and MBC was 120 ppm) the diameter of the inhibition zone increased as the concentration increased. It was toxic at high concentrations and nontoxic at low concentrations. Conclusion: Nano-silver fluoride is a good material to be used in arresting and preventing dental caries and it is safe to be used on humans.